Penerapan Metode HIRA dan Fishbone Diagram Pada Praktek Siswa SMK Yang Menimbulkan Risiko Kecelakaan Kerja Pada Bengkel Ototronik SMK - Afiff Yudha Tripariyanto; Sri Rahayuningsih (JATI UNIK : Jurnal Ilmiah Teknik dan Manajemen Industri, 2020)
Vocational High School is one of the education levels equivalent to senior high school which is printed and prepared to become skilled workers in the field. Ototronik is a vocational field which includes a lot to learn about automotive electronic systems. This study aims to determine the potential hazards that have the highest risk value as many as 3 types of work accidents in labs in the Private Vocational Laboratory in the Loceret Nganjuk area in accordance with the Risk Rating Number and provide recommendations for improvement on the types of activities that have the highest risk value as many as 3 types of work accidents in activities practicum at the Private Vocational Laboratory in the Loceret Nganjuk area using the Fishbone Diagram. The research method uses the Hazard Identification And Risk Assessment (HIRA) method and Fishbone Diagram. From the results of the study, the types of activities that have the highest Risk Rating Number are tripping Spare Parts / workshop tools with a Risk Rating Number of 8, tripping handtool / work tools with a Risk Rating Number of 8 and breathing in smoke with a Risk Rating Number of 8. Of the three types These activities are categorized as medium priority risk level / significant risks entered in index III B, namely the occurrence of unwanted potential. Then an analysis is carried out using a Fishbone Diagram by providing recommendations, namely conducting activities in a laboratory carefully and always using PPE as well as complying with the rules and knowing the functions of each - each Spare Part, work equipment and sharp-smelling objects. Sekolah Menengah Kejuruan merupakan salah satu jenjang pendidikan setara sekolah menengah atas yang dicetak dan disiapkan untuk menjadi tenaga tenaga terampil pada bidangnya. Ototronik adalah salah satu kejuruan yang didalamnya banyak belajar tentang sistem otomotif elektronika. Penelitian ini bertujuan untuk mengetahui potensi bahaya yang memiliki nilai risiko tertinggi sebanyak 3 jenis kecelakaan kerja pada praktikum di Laboratorium SMK Swasta didaerah Loceret Nganjuk sesuai dengan Risk Rating Number dan memberikan rekomendasi perbaikan pada jenis kegiatan yang memiliki nilai risiko tertinggi sebanyak 3 jenis kecelakaan kerja di kegiatan praktikum di Laboratorium SMK Swasta didaerah Loceret Nganjuk menggunakan Diagram Fishbone. Pada metode penelitian menggunakan metode Hazard Identification And Risk Assessment (HIRA) dan Fishbone Diagram. Dari hasil penelitian, yaitu jenis kegiatan yang memiliki Risk Rating Number tertinggi adalah tersandung sparepart/ alat bengkel dengan Risk Rating Number sebesar 8, tersandung handtool/ alat kerja dengan Risk Rating Number sebesar 8 dan menghirup asap dengan Risk Rating Number sebesar 8. Dari ketiga jenis kegiatan tersebut dikategorikan tingkat risiko prioritas menengah/ risiko signifikan masuk pada indeks III B yaitu terjadinya potensi tidak diinginkan.Kemudian dilakukan analisis menggunakan Diagram Fishbone dengan memberikan rekomendasi yaitu melakukan kegiatan dilaboratorium secara hati – hati dan selalu menggunakan APD serta mematuhi aturan dan mengetahui fungsi dari masing – masing sparepart, peralatan kerja dan benda – benda berbau tajam.